Starin profile effects on the time rate of consolidation settlements. - Zarco, Mark H. (UPCOE NEC Technical Bulletin)
Consolidation settlements are a major consideration in the design of structures founded on soft clays. At present, analytical procedures used to estimate the rate at which these settlements occur are limited to cases involving uniform strain conditions under constant surcharge. In this paper, two procedures that consider effects of non-uniform strain profile on the time rate of consolidation settlements due to a time-dependent load are presented. Numerical experiments performed indicate that the rates of consolidation settlement predicted by the modified methods are in better agreement with field experience when compared to current analytical methods.